A new English translation of the Septuagint : and the other Greek translations traditionally included under that title - Pietersma, Albert; Wright, Benjamin G., III (Oxford University Press, 2007)
Translated from the Hebrew between the third and first centuries B.C., the Septuagint became the Bible for Greek-speaking Jews and was widely cited by early Christians. Now, at long last, it has been made available in an accurate modern translation for English readers.-